Motion artifact variability in biomagnetic wearable devices - Ghahremani Arekhloo, Negin; Wang, Huxi; Parvizi, Hossein; Tanwear, Asfand; Zuo, Siming; McKinlay, Michael; Garcia Nuñez, Carlos; Nazarpour, Kianoush; Heidari, Hadi (Frontiers in Medical Technology, 2024)
Motion artifacts can be a significant noise source in biomagnetic measurements when magnetic sensors are not separated from the signal source. In ambient environments, motion artifacts can be up to ten times stronger than the desired signals, varying with environmental conditions. This study evaluates the variability of these artifacts and the effectiveness of a gradiometer in reducing them in such settings. To achieve these objectives, we first measured the single channel output in varying magnetic field conditions to observe the effect of homogenous and gradient background fields. Our analysis revealed that the variability in motion artifact within an ambient environment is primarily influenced by the gradient magnetic field rather than the homogeneous one. Subsequently, we configured a gradiometer in parallel and vertical alignment with the direction of vibration (X-axis). Our findings indicated that the singlechannel sensor output exhibited a change of 164.97 pT per mm unit increase in the gradient background magnetic field, while the gradiometer output only showed a change of 0.75 pT/mm within the range of 1 nT/mm to 10 nT/mm. Upon repositioning the gradiometer vertically (Y direction), perpendicular to the direction of vibration, the single-channel output slope increased to 196.85 pT, whereas the gradiometer output only increased by 1.06 pT/mm for the same range. Our findings highlight the influence of ambient environments on motion artifacts and demonstrate the potential of gradiometers to mitigate these effects. In the future, we plan to record biomagnetic signals both inside and outside the shielded room to compare the efficacy of different gradiometer designs under varying environmental conditions.